Enhancing Endocrine Therapy Combination Strategies for the Treatment of Postmenopausal HR+/HER2– Advanced Breast Cancer. (January 2017) - Pritchard, Kathleen I.; Chia, Stephen K.; Simmons, Christine; McLeod, Deanna; Paterson, Alexander; Provencher, Louise; Rayson, Daniel
Abstract: Breast cancer (BC) is the most common malignancy in women worldwide, with approximately two‐thirds having hormone receptor‐positive (HR+) tumors. New endocrine therapy (ET) strategies include combining ET agents as well as adding inhibitors targeting growth factors, angiogenesis, the mechanistic target of rapamycin, phosphoinositide 3‐kinase (PI3K), or cyclin‐dependent kinase 4/6 to ET. Level 1 evidence supports use of fulvestrant plus anastrozole or palbociclib plus letrozole as first‐line therapy for HR+/HER− advanced BC with special consideration for the former in ET‐naïve patients, as well as everolimus plus exemestane or palbociclib plus fulvestrant as second‐line therapy with special consideration in select first‐line patients. Although the safety profiles of these combinations are generally predictable and manageable, both everolimus and palbociclib are associated with an increased risk of potentially serious or early‐onset toxicities requiring individualized a priori adverse event risk stratification, earlier and more rigorous agent‐specific monitoring, and patient education. Although each of these combinations improves progression‐free survival, none with the exception of anastrazole plus fulvestrant have demonstrated improved overall survival. PI3K catalytic‐α mutations assessed from circulating tumor DNA represent the first potentially viable serum biomarker for the selection of ET combinations, and new data demonstrate the feasibility of this minimally invasive technique as an alternative to traditional tissue analysis. Therapeutic ratios of select ET combinations support their use in first‐ and second‐line settings, but optimal sequencing has yet to be determined. The Oncologist 2017;22:12–24 Implications for Practice: Emerging data show that new endocrine therapy (ET) combinations can improve progression‐free and overall survival outcomes in patients with hormone receptor‐positive, HER2‐negative (HR+/HER−) advanced breast cancer. Level 1 evidence supports consideration of dual ET regimens, particularly in ET‐naïve patients, or palbociclib plus letrozole as first‐line therapy, as well as the addition of mTOR or CDK4/6 inhibitors to established ET in the second‐line setting and in select first‐line patients. Some combinations are associated with increased risk of class‐specific toxicities that will require individualized risk stratification, earlier and more rigorous agent‐specific monitoring, and patient education. Recent data on a noninvasive biomarker assay that predicts response to a phosphoinositide 3‐kinase inhibitor demonstrates the feasibility of this minimally invasive technique as an alternative to traditional tissue analysis. Abstract : Evidence supports use of first‐line dual endocrine therapy (ET) regimens, particularly in ET‐naïve patients, or palbociclib plus letrozole, as well as everolimus plus exemestane or palbociclib plus fulvestrant as second‐line therapy for HR‐positive, HER2‐negative advanced breast cancer. Some combinations are associated with increased risk of class‐specific toxicities.